Hopf galois extensions - Erey, Nursel. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Let H be a Hopf algebra which coacts to the right on A and let B be the subalgebra of coinvariants. The extension B A is said to be Hopf Galois if the canonical map ..... is a bijection. This work investigates this kind of extension for special coactions.
Keywords: Hopf algebras.; Galois theory.